The Biology of Demodecid Mites (Trombidiformes: Demodecidae) and Their Parasitism in the Eurasian Beaver Castor fiber Linnaeus, 1758, with a Description of a New Species - Leszek Rolbiecki; Joanna N. Izdebska; Joanna Dzido; Sławomira Fryderyk (Animals)
The largest Eurasian rodent, the Eurasian beaver Castor fiber, is known for its amphibious lifestyle that allows it to adapt its environment to its needs. Due to its lifestyle and evolutionary history, the beaver is characterized by a distinct, unique parasitofauna. In this context, the occurrence of mites from the Demodecidae family in the Eurasian beaver was investigated. The topography of the Demodex castoris was analyzed: it was previously known from a single record from a single skin location of this host. The mite was found in large numbers in various locations in the hairy skin, including the head, trunk, and limbs. In addition, a new species associated with hairless skin, mainly around the mouth, was discovered and described: Demodex ovaportans sp. nov. The females of this species carry the egg on the dorsal side of the podosoma, which may be a form of care and a previously unknown reproductive strategy in Demodecidae. Our findings confirm that a host-specific demodecid mite species associated with the hairy skin of the entire body is a universal model in mammals. They also emphasize the uniqueness of the beaver parasitofauna, as evidenced by the host specificity and the different biology of the demodecids described in it.